Is Initial Board Certification Associated With Better Early Career Surgical Outcomes?. Issue 2 (August 2021) - Kendrick, Daniel E.; Chen, Xilin; Jones, Andrew T.; Clark, Michael; Fan, Zhaohui; Bandeh-Ahmadi, Hoda; Wnuk, Greg; Kopp, Jason P.; Moreno, Beatriz Ibanez; Scott, John W.; Sandhu, Gurjit; Buyske, Jo; et al.
Abstract : Objective: To determine if initial American Board of Surgery certification in general surgery is associated with better risk-adjusted patient outcomes for Medicare patients undergoing partial colectomy by an early career surgeon. Background: Board certification is a voluntary commitment to professionalism, continued learning, and delivery of high-quality patient care. Not all surgeons are certified, and some have questioned the value of certification due to limited evidence that board-certified surgeons have better patient outcomes. In response, we examined the outcomes of certified versus noncertified early career general surgeons. Methods: We identified Medicare patients who underwent a partial colectomy between 2008 and 2016 and were operated on by a non-subspecialty trained surgeon within their first 5 years of practice. Surgeon certification status was determined using the American Board of Surgery data. Generalized linear mixed models were used to control for patient-, procedure-, and hospital-level effects. Primary outcomes were the occurrence of severe complications and occurrence of death within 30 days. Results: We identified 69, 325 patients who underwent a partial colectomy by an early career general surgeon. The adjusted rate of severe complications after partial colectomy by certified (n = 4239) versus noncertified (n = 191) early-career general surgeons was 9.1% versus 10.7% (odds ratio 0.83, P = 0.03). Adjusted mortality rate for certified versus noncertified early-career general surgeons was 4.9% versus 6.1% (odds ratio 0.79, P = 0.01). Conclusion: Patients undergoing partial colectomy by an early career general surgeon have decreased odds of severe complications and death when their surgeon is board certified. Abstract : Supplemental Digital Content is available in the text